Regulatory Networks in Seeds Integrating Developmental, Abscisic Acid, Sugar, and Light Signaling - Brocard-Gifford, Inès M. (American Society of Plant Biologists, 2003)
Progression through embryogenesis and the transition to germination is subject to regulation by many transcription factors, including those encoded by the Arabidopsis LEC1 (LEAFY COTYLEDON1), FUS3 (FUSCA3), and abscisic acid-insensitive (ABI) ABI3, ABI4, and ABI5 loci. To determine whether the ABI4, ABI5, LEC1, and FUS3 loci interact or act independently, we analyzed abi fus3 and abi lec1 double mutants. Our results show that both ABI4 and ABI5 interact genetically with both LEC1 and FUS3 in controlling pigment accumulation, suppression of vivipary, germination sensitivity to abscisic acid, gene expression during mid- and late embryogenesis, sugar metabolism, sensitivity to sugar, and etiolated growth. However, the relative strengths of the observed interactions vary among responses and may even be antagonistic. Furthermore, the interactions reveal cryptic effects of individual loci that are not detectable by analyses of single mutants. Despite these strong genetic interactions, but consistent with the disparities in peak expression of these loci, none of the ABI transcription factors appear to interact directly with either FUS3 or LEC1 in a yeast (Saccharomyces cerevisiae) two-hybrid assay system.